Eastern USA - Balfour, Amy C.; Karlin, Adam.; O'Neill, Zora.; Raub, Kevin; St Louis, Regis; Vorhees, Mara.; Lonely Planet Publications (Firm) (Lonely Planet, 2016)
Highlights the eastern U.S.'s top travel experiences, providing a monthly calendar of popular events, road trip and scenic drive ideas, and information on sights, dining, accommodations, shopping, and entertainment in each area profiled.
Keywords: East (U.S.) -- Guidebooks; East (U.S.) -- Description and travel; Travel; East (U.S.); Guidebooks